2011
DOI: 10.1080/02640414.2010.520727
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity recommendations and cardiovascular disease risk factors in young Hispanic women

Abstract: Despite the benefits associated with regular physical activity, there is little epidemiological evidence to support positive health outcomes when meeting physical activity guidelines in high-risk ethnic groups, such as Hispanic women. We compared cardiovascular disease risk factors between young Hispanic women who meet and those who do not meet current physical activity guidelines. Height, weight, waist circumference, and blood pressure were measured in 60 Hispanic women aged 20-39 years. Lipids, C-reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…While research suggests that PA reduces BMI and total body fat in Latinos (ref. 17 20 ), data regarding VAT are sparse. Given the higher prevalence of obesity among Latinos (42.5%) compared to whites (32.6%), and the significant increase in the prevalence of obesity among Latinos from 1999–2010 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…While research suggests that PA reduces BMI and total body fat in Latinos (ref. 17 20 ), data regarding VAT are sparse. Given the higher prevalence of obesity among Latinos (42.5%) compared to whites (32.6%), and the significant increase in the prevalence of obesity among Latinos from 1999–2010 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies examining the effects of PA interventions with Latinos reveal mixed findings [24]. Positive outcomes have included improvements in BMI [25], total cholesterol (Total-C) [26, 27], lower triglycerides (TG), higher fat-free mass, maximum aerobic fitness (VO 2max ) [28], and increased activity levels [29-31]. However, a limitation of many prior studies is self-report of PA levels [32].…”
Section: Introductionmentioning
confidence: 99%
“…Publication dates ranged from 2001 to 2021. Out of 23 studies, 14 studies were cross-sectional designs [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and 9 were interventional studies [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] (random experiment: 5 [ 51 , 52 , 54 , 56 , 57 ] and non-random experiment: 4 [ 50 , 53 , 55 , 58 ]). Intervention length ranged from 1 week [ 55 ] to 24 months [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total sample size was 2105, ranging from 10 [ 55 ] to 535 [ 42 ] participants. The mean age ranged from 21.4 [ 50 ] to 62.8 years [ 49 ], with 8 studies [ 36 , 38 , 39 , 43 , 45 , 47 , 48 , 50 ] focused on the young and 10 studies focused on the middle-aged [ 37 , 41 , 42 , 44 , 49 , 51 , 52 , 56 , 57 , 58 ]. There were 11 studies that reported menstrual status, with 4 including post-menstruation [ 37 , 49 , 52 , 56 ], 5 including pre-menstruation [ 38 , 39 , 41 , 43 , 45 ], and 2 including both [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation